PyTorch Computer Vision Cookbook : Over 70 recipes to master the art of computer vision with deep learning and PyTorch 1.x /: Over 70 recipes to master the art of computer vision with deep learning and PyTorch 1.x. (2020) - Avendi, Michael
No abstract available